Cross-Cultural Politeness in Indonesian and Uzbek Communication: A Linguo-Pragmatic Perspective - Hulkar Turdieva Komilovna; Samigov Boburjon Asrarjonovich; Azizah Des Derivanti (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2025)
Background Politeness is a key element of communication that reflects cultural identity, social values, and interpersonal ethics. In both Indonesia and Uzbekistan, politeness plays a crucial role in maintaining harmony and respect, yet it is realized differently due to variations in cultural norms and interactional styles. Methodology This study employs a linguo-pragmatic comparative approach based on Brown and Levinson’s politeness theory and Goffman’s concept of face. Data were collected through natural observations, recorded conversations, and questionnaires with 120 participants from Indonesia and Uzbekistan. The analysis focused on verbal and nonverbal expressions of politeness in daily communication, marketplace interactions, and hospitality situations. Findings The results show that Indonesian speakers tend to use negative politeness strategies emphasizing moderation, indirectness, and hierarchical respect. In contrast, Uzbek speakers prefer positive politeness strategies characterized by expressiveness, warmth, and repeated offers. Both cultures regard politeness as a reflection of communal and moral values, although they differ in the pragmatic realization and social intensity of politeness. Conclusion Politeness in both societies serves as a tool for sustaining harmony and social cohesion. The study confirms that Brown and Levinson’s theory remains relevant but must be contextualized within Asian collectivist pragmatics to fully capture the moral and relational dimensions of politeness in Muslim-majority societies. Originality This research offers one of the first comparative linguo-pragmatic analyses of Indonesian and Uzbek politeness, contributing new insights into intercultural Communication, pragmatic competence, and culturally responsive language education.